Availability of thrombolytic therapy in rural Newfoundland and Labrador. - Marshall, S (1995)
OBJECTIVE: To determine the availability of thrombolytic therapy in rural Newfoundland and Labrador. DESIGN: Self-administered questionnaire mailed to staff at health care facilities. Respondents were sent two reminders by mail, and questionnaires not returned were completed through telephone interviews. SETTING: Rural health care facilities, including hospitals, 24-hour clinics and satellite clinics. PARTICIPANTS: All chief medical officers, nursing supervisors and administrators in the 34 government-funded rural health care facilities in Newfoundland and Labrador. OUTCOME MEASURES: Number of facilities offering thrombolytic therapy to patients with acute myocardial infarction (AMI) in 1992. For each facility: number of patients presenting with AMI during that year, number of these patients who received thrombolytic therapy, number of staff trained in advanced cardiac life support, travel time to the nearest referral centre, population served and number of beds. RESULTS: Of the 34 rural health care facilities in Newfoundland and Labrador, 91% (31/34) responded to the survey. Thrombolytic therapy was offered in 93% (13/14) of the rural hospitals, 22% (2/9) of the 24-hour clinics and none of the single-physician satellite clinics. In 1992, 390 patients with AMI presented to these health care facilities; 39% of these patients presented to facilities that did not offer thrombolytic therapy. CONCLUSIONS: Thrombolytic therapy has been successfully introduced in many of the rural and isolated health care facilities in Newfoundland and Labrador. An important factor in this success is continuing medical and nursing education on the effectiveness of thrombolytic therapy and the skills needed to provide it. Cost-effectiveness data are needed to determine whether it is reasonable to offer this therapy in isolated, low-volume clinics. More research on the outcomes in patients receiving thrombolytic therapy in rural facilities is also needed.